Reasons given by patients for participating, or not, in Phase 1 cancer trials. - Catt, S; Langridge, C; Fallowfield, L; Talbot, D; Jenkins, V (2011)
BACKGROUND: Communication with patients contemplating Phase 1 cancer trial participation can be challenging. Controversy exists as to whether they are provided with sufficient information to give genuinely informed consent. We present data examining the reasons patients gave for trial entry. METHOD: Following discussions with oncologists about Phase 1 trials, participants completed a 19-item study specific 'accept or decline measure' exploring hope, expectations of benefit, altruism, concerns, and general perceptions of the trial information. They also completed 2 standardised questionnaires measuring psychological morbidity and predisposition towards optimism. RESULTS: Forty patients completed the study questionnaires. Patients were generally optimistic with few concerns about the experimental nature of Phase 1 trials. Most 36/40 (90%) consented to trial entry. Fifty-one percent thought the trial was the only treatment option available. The four main reasons for trial entry were: expectation of some medical benefit (21%); trial the best available option (21%); to maintain hope (15%) and to help with research (13%). Only one patient gave altruism as their main reason for trial participation. CONCLUSION: Patients considering Phase 1 trials may be a self-selected group with optimistic expectations of personal benefit driving trial entry rather than altruism. Achieving genuinely informed consent and avoidance of therapeutic misconceptions in such patients may be difficult.